2021
DOI: 10.1016/j.ajhg.2021.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Mosaic human preimplantation embryos and their developmental potential in a prospective, non-selection clinical trial

Abstract: Summary Chromosome imbalance (aneuploidy) is the major cause of pregnancy loss and congenital disorders in humans. Analyses of small biopsies from human embryos suggest that aneuploidy commonly originates during early divisions, resulting in mosaicism. However, the developmental potential of mosaic embryos remains unclear. We followed the distribution of aneuploid chromosomes across 73 unselected preimplantation embryos and 365 biopsies, sampled from four multifocal trophectoderm (TE) samples and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
110
2
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 160 publications
(121 citation statements)
references
References 33 publications
7
110
2
2
Order By: Relevance
“…Embryo chromosome status is a key variable, but in situations when euploid embryos are not available, any available mosaic embryos can be transferred with good outcomes. 29,30 The decision to test or not test or to transfer or not transfer any embryo, however, is ultimately a clinical decision linked to patient-specific situations and should be left in the hands of the informed clinician, following discussion(s) with their patient. 36 PGT-A can improve initial transfer outcomes when performed well, simply because euploid embryos are more successful than other embryos.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Embryo chromosome status is a key variable, but in situations when euploid embryos are not available, any available mosaic embryos can be transferred with good outcomes. 29,30 The decision to test or not test or to transfer or not transfer any embryo, however, is ultimately a clinical decision linked to patient-specific situations and should be left in the hands of the informed clinician, following discussion(s) with their patient. 36 PGT-A can improve initial transfer outcomes when performed well, simply because euploid embryos are more successful than other embryos.…”
Section: Discussionmentioning
confidence: 99%
“…The area is divided into four quadrants based around the group mean routine IVF IR outcomes for 2018 and the mean for just the euploid embryo transfers from this study (black dots, grouped by colored clouds). Results for seven other cited studies [6][7][8]10,12,27,28 (red stars) with IR data for Preimplantation Genetic Testing -Aneuploidy (PGT-A) and IVF groups and three other cited studies 15,29,30 (blue stars) with PGT-A IR data only are shown for comparison. Circled dots represent clinically significant differences to the means.…”
Section: Affect On Rctsmentioning
confidence: 99%
“…All CMs related to autosomal chromosomes were classified into the group of autosomal abnormalities, whereas CMs related to sex chromosomes were classified into the group of sex chromosomal abnormalities. With respect to the CM fraction, we defined a fraction greater than or equal to 50% as high and others as low ( Bellil et al, 2020 ; Capalbo et al, 2021 ). As the results of karyotyping which were counted manually may introduce human error, the classification of the CM fraction was performed based on the results of CMA.…”
Section: Methodsmentioning
confidence: 99%
“…One of the most intriguing questions currently being addressed by research is the selective elimination of aneuploid cells, suggested by normal live births after the intrauterine transfer of mosaic aneuploid embryos [ 16 , 20 ]. Experiments on extended blastocyst cultures showed that a high proportion (71%) of embryos originally diagnosed as mosaic were found to be euploid [ 165 ].…”
Section: Stem Cell-based Studies Of Chromosomal Aneuploidy and Mosaic...mentioning
confidence: 99%
“…Data from preimplantation genetic testing (PGT) show that embryos with mosaic karyotypes can develop and produce chromosomally normal fetuses [ 16 , 17 , 18 , 19 , 20 , 21 ]. In some studies, it has been found that, in mosaic embryos, aneuploid cells are located predominantly in the trophectoderm/trophoblast lineage [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%